E-047 Distal Emboli Following ERIC Thrombectomy. (29th July 2016) - Chueh, J; Marosfoi, M; Langan, E; Puri, A; Gounis, M
Abstract : Introduction: The use of clot retrievers during mechanical endovascular treatment of acute ischemic stroke can cause clot fragmentation with the release of distal emboli. It was our hypothesis that the risk of embolic shower may potentially be altered using the Embolus Retriever with Interlinked Cages (ERIC®) thrombectomy system. The objective of this study was the characterization of distal emboli generated during ERIC® thrombectomy device use as a function of access approach. Materials and methods: A hard, inelastic clot was prepared and injected into an anatomically correct circle of Willis (CoW) replica to form a middle cerebral artery occlusion. Thrombectomy was conducted per the manufacturer's instructions in four different groups (n = 10), each exploring different variables. In group 1, thrombectomy was performed using the ERIC ® through an 8 F balloon guide catheter (BGC) positioned at the cervical ICA (ERIC®+BGC). In group 2, thrombectomy was performed using the ERIC® in conjunction with thromboaspiration via a 6 F Sofia intermediate catheter at the origin of the MCA (ERIC®+SOFIA). In group 3, thrombectomy was performed using the Solitaire in conjunction with thromboaspiration via a 6 F Sofia intermediate catheter at the origin of the MCA (Solitaire+SOFIA). Group 4 used the same setup as group 2 with the addition of proximal ICA flow arrest using a BGC during clot removal (ERIC®+SOFIA+BGC). Emboli smaller than 1000 µm was characterized using the Coulter Principle. The primary endpoints were the size and quantity of the clot fragments generated during the procedure and the secondary endpoints were the flow recanalization rate and time to recanalization. Results: Formation of large emboli greater than 1000 μm in size occurred in 2 out of 10 cases in the ERIC®+BGC group, versus 7, 6 and 5 of 10 experiments with the ERIC®+SOFIA, Solitaire+SOFIA, ERIC®+SOFIA+BGC groups, respectively. The ERIC®+BGC group marginally reduced the number of emboli having a diameter >200 μm (p = 0.064), with a total of 5 particles, as compared to the ERIC®+Sofia, Solitaire+Sofia, and ERIC®+Sofia+BGC groups that produced 20, 17 and 16 fragments >200 μm, respectively. On average, in the size range between 100–200 μm and 50–100 μm, ERIC®+Sofia showed a trend to reduce clot fragments as compared with the other 3 treatment strategies; however, these results were not statistically significant (p > 0.05). There were no significant differences in particle number between any of the groups for particles with size <50 μm. A complete flow restoration after a single pass was observed in all cases except for two experiments in the Solitaire + Sofia group, which required two passes to achieve full recanalization. Without waiting for 4 minutes prior to clot removal, thrombectomy with the ERIC® allows shorter time to recanalization as compared to the Solitaire. Conclusion: Based on this preliminary study, it is our conclusion that the techniques of ERIC®+BGC, ERIC®+Sofia, Solitaire+Sofia, and ERIC®+SOFIA+BGC are all similar with regard to clot fragmentation. Combining all particulates in the most dangerous range (>200 μm), there was a marginal reduction in the number of distal emboli with the use of ERIC® and BGC (p = 0.064). Disclosures: J. Chueh: None. M. Marosfoi: None. E. Langan: None. A. Puri: 1; C; Medtronic Neurovascular, Stryker Neurovascular. 4; C; InNeuroCo. M. Gounis: 1; C; National Institutes of Health, Codman Neurovascular, Stryker Neurovascular, Microvention, Medtronic Neurovascular, Philips Healthcare, InNeuroCo, Neuronal Protection Systems, the Wyss Institute, Silk Road. 2; C; Codman Neurovascular, Stryker Neurovascular. 4; C; InNeuroCo.